2004
DOI: 10.1097/01.iop.0000117337.65340.e5
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Benign Mixed Tumor (Chondroid Syringoma) of the Eyelid: Clinical Presentation and Management

Abstract: Cutaneous benign mixed tumor may occur in the eyelid, and, although uncommon, should be included in the differential diagnosis of firm, nodular eyelid tumors. The histopathologic features are similar to those seen in this tumor type arising in other areas of the body. Preoperative consideration of this diagnostic possibility may allow the surgeon to plan for complete excision, thereby reducing the possibility of recurrence or malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Around 75% of cutaneous pleomorphic adenomas, also called chondroid syringomas, arise from the head and neck region [22]. Although the stromal component of the tumor has been postulated to be derived from the myoepithelial cells of the outer layer of the ductules, Mandeville et al [23] reported that in some patients, histological examination of the tumor revealed both eccrine and apocrine characteristics; therefore, the origin of the tumor is uncertain. In the management of such nodular lesions, differential diagnoses should include other cutaneous lesions, such as epidermal cysts, pilomatricoma, dermoid cysts, sebaceous cysts, neurofibroma, and even basal cell carcinoma [24].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Around 75% of cutaneous pleomorphic adenomas, also called chondroid syringomas, arise from the head and neck region [22]. Although the stromal component of the tumor has been postulated to be derived from the myoepithelial cells of the outer layer of the ductules, Mandeville et al [23] reported that in some patients, histological examination of the tumor revealed both eccrine and apocrine characteristics; therefore, the origin of the tumor is uncertain. In the management of such nodular lesions, differential diagnoses should include other cutaneous lesions, such as epidermal cysts, pilomatricoma, dermoid cysts, sebaceous cysts, neurofibroma, and even basal cell carcinoma [24].…”
Section: Discussionmentioning
confidence: 98%
“…In the management of such nodular lesions, differential diagnoses should include other cutaneous lesions, such as epidermal cysts, pilomatricoma, dermoid cysts, sebaceous cysts, neurofibroma, and even basal cell carcinoma [24]. Wide excision of tumor is considered to be the best management [23].…”
Section: Discussionmentioning
confidence: 99%
“…[610] The classification of these tumors into an apocrine type or eccrine type relies on the histopathological appearance of the glandular component. Comparable to our case, the tumor may originate from the apocrine sweat glands, where the glandular epithelial component is lined by a double layer of cuboidal epithelial cells arranged in islands, chords or tubules.…”
Section: Discussionmentioning
confidence: 99%
“…This relatively uncommon tumor rarely affects the ocular adnexa. 2 To our knowledge, chondroid syringoma arising from the lower eyelid with severe ectropion is highly unusual.…”
mentioning
confidence: 95%
“…2 In 1961, Hirsch and Helwig 3 introduced the term chondroid syringoma to describe this tumor, which is characterized by the presence of sweat gland elements lying within a cartilage-like stroma. 2 This benign skin adnexal tumor usually develops as a slowly growing intradermal or subcutaneous nodule on the face. This relatively uncommon tumor rarely affects the ocular adnexa.…”
mentioning
confidence: 99%